Anti-gender politics and the authoritarian turn in Brazil - Gomes da Costa Santos, Gustavo (Brasiliana: Journal for Brazilian Studies, 2021)
In 2018, Jair Bolsonaro, a former captain and congressman known for his racist, sexist, and homophobic remarks, was elected president of Brazil. His election shocked political analysts, representing the major setback in the Brazilian democracy since the end of the military rule in the 1980’s. The present work analyses the social actors and the political processes behind the rise of Bolsonaro to power. It focuses on the role of anti-gender politics in the recent authoritarian turn. Borrowing some insights from the Protest Event Analysis methodology, the work explores the dynamics of the anti-gender protest events, their main social and political actors, repertoires of actions and demands. It also review the recent debate on the crisis of democracy and the rise of extreme right-wing movements and parties, focusing on the centrality of opposition to gender equity and LGBTQI+ rights in the rhetoric and action of conservative and far-right groups.